TINJAUAN PELAKSANAAN PENGISIAN INFORMED CONSENT PADA KASUS BEDAH ORTHOPEDI DI RS PKU MUHAMADIYAH GAMPING SLEMAN YOGYAKARTA - Wuryanto, Sis; Khodijah, Nurul (MEDIA ILMU KESEHATAN, 2016)
Background: Physicians should provide clear information to the patients and/or their families before undertaking significant intrerventions. Informed consent sheets must be completed and signed as one of the legal aspects in medical practice. Based on a preliminary study conducted in June 2016 at RS PKU Muhamadiyah Gamping, the application of informed consent was incomprehensive. Objectives: To analyze the information supplied to the patients and identify factors inhibiting the implementation of informed consent in orthopedic surgery cases at RS PKU Muhamadiyah Gamping. Methods: This research was descriptive qualitative with cross sectional approach. Subjects consisted of one surgical nurse, two medical record officers, and one head of the medical record. The study employed purposive sampling on April-June year of 2016 informed consent sheets, comprised 57 of informed consent sheets. Result: Information that is often provided by the physicians to the patients included diagnosis, objectives, interventions, prognosis and complications. However, alternatif interventions and others were not completely informed to the patients. Barriers to implement complete and thorough informed consent was the physicians’ limited time and the low level of patients’ knowledge. Conclusion: Physicians had provided rigorous information on diagnosis, objectives, interventions, prognosis and complications, but less information on the alternatif interventions and others. The physicians’ time constraint and patients’ knowledge level had been two factors that inhibited the thorough use of informed consent.